Modeling the Kinetics of Protein Conjugation Reactions1. Issue 11 (11th October 2016) - Pfister, David; Ulmer, Nicole; Klaue, Antoine; Ingold, Oliver; Morbidelli, Massimo
Abstract: Over the past decades, the pharmaceutical industry has shown a continuous infatuation for therapeutic proteins. In order to constantly improve their efficacy, chemical reactions involving the conjugation of the therapeutic protein with various chemical reagents have been developed. Little efforts have been put forth to simulate the kinetics of protein conjugation and the literature dealing with kinetic models is rather scarce as compared to the abundant references about conjugation reactions in general. In this work, techniques to measure the kinetics of reaction, model the conjugation between add‐on molecules and proteins, and evaluate the model parameters are discussed. Abstract : Due to the complex nature of proteins, which often bear multiple reactive sites, the kinetic modeling of conjugation reactions can be quite challenging. This work presents a rigorous approach for modeling these reactions and ultimately gain a better understanding of the underlying mechanisms and design more efficient processes.